2010
DOI: 10.1254/jphs.09277fp
|View full text |Cite
|
Sign up to set email alerts
|

A Novel CC-Chemokine Receptor 3 Antagonist, Ki19003, Inhibits Airway Eosinophilia and Subepithelial/Peribronchial Fibrosis Induced by Repeated Antigen Challenge in Mice

Abstract: Abstract. CC-chemokine receptor 3 (CCR3) is a chemokine receptor for which major ligands, CC-chemokine ligand (CCL) 11, CCL24, and CCL26, are known to be involved in chemotaxis for eosinophils. In the present study, we evaluated the effect of a low molecular weight CCR3-receptor antagonist, Ki19003 (4-[[5-(2,4-dichlorobenzylureido)pentyl][1-(4-chlorophenyl)ethyl]amino]butanoic acid), on airway remodeling in a mouse model of allergic asthma. BALB/c mice were sensitized twice by intraperitoneal injection of oval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 54 publications
(48 reference statements)
0
20
0
1
Order By: Relevance
“…The airways of patients with asthma have been shown to contain higher numbers of cells expressing mRNA for CCR3 and its ligands, compared to non-asthmatic control subjects (9). In mouse models of allergic airway inflammation, antigen-induced airway eosinophilia may be inhibited by the administration of either a monoclonal antibody against CCR3 (10) or a low molecular weight CCR3-antagonist (11). …”
Section: Eosinophil Surface Molecules and Receptorsmentioning
confidence: 99%
“…The airways of patients with asthma have been shown to contain higher numbers of cells expressing mRNA for CCR3 and its ligands, compared to non-asthmatic control subjects (9). In mouse models of allergic airway inflammation, antigen-induced airway eosinophilia may be inhibited by the administration of either a monoclonal antibody against CCR3 (10) or a low molecular weight CCR3-antagonist (11). …”
Section: Eosinophil Surface Molecules and Receptorsmentioning
confidence: 99%
“…CCchemokine receptor 3 (CCR3) is an eotaxin receptor known to be involved in eosinophil chemotaxis. Komai et al reported that CCR3 antagonism not only prevents the infiltration of eosinophils into the airways but also prevents the development of allergen-induced subepithelial and peribronchial fibrosis in mouse models [139]. IL-4 and IL-13 are two cytokines produced by activated CD4 + T cells and are important in the development of allergic responses [140].…”
Section: Potential Future Treatment Targetsmentioning
confidence: 99%
“…Heparin in various forms inhibits leukocyte recruitment to mouse models of arthritis, traumatic brain injury and lipopolysaccharide (LPS) treatment [106][107][108], although its effectiveness depends upon the dose given and the duration of inflammation [109]. These studies show potential role of GAG mimetics on chemokine-mediated immunomodulation when administered, either local or systemically, however it should be noted that administered heparin is likely to interact with all cytokines due to its highly negative charge, and a more chemokine-specific gradient disruption method could be more beneficial.…”
Section: Competitive Displacement Of Chemokinesmentioning
confidence: 99%